Bullying and Social Exclusion of Students with Special Educational Needs in Primary Education Schools - Álvaro Carmona; Manuel Montanero (Social Sciences)
Children’s safety, well-being and inclusion in the school environment can be severely impacted by social isolation and bullying. This study examined these threats in a sample of 14 group-classes (291 students) from four different primary education schools. A total of 44 special educational needs (SEN) students and 44 students without SEN were selected. The social network structure of each group-class was analysed, as well as the number of friendship ties, the degree of emotional well-being and social participation (both inside and outside of the school), and the possible cases of bullying. The results show a significantly greater rate of social rejection, emotional distress and risk of exclusion in SEN students with respect to their peers, as well as a considerably higher perception of bullying (38.6% vs. 4.8%). The SEN students who reported bullying were mostly schooled in social networks with a more segregated and fragmented structure. Moreover, the mean value obtained in these groups was lower for all the analysed indicators, although the differences were not statistically significant. These data support the idea that the social capital of the group class could influence the prevention of violence and bullying towards SEN students. However, further studies with larger samples are needed to confirm this. Lastly, strategies to promote the social inclusion of SEN students in primary education schools are discussed.